A systems immunology perspective on gout pathogenesis and its precision-targeted treatment strategies - Chen, Zilong; Guo, Qian; Zhang, Yanzhao; Chen, Lulu; Li, Puyu; Cheng, Wenfei; Liu, Chuanxin; Jiang, Hongwei (Frontiers in Immunology, 2025)
Gouty arthritis (GA) is a sterile inflammatory disease driven by monosodium urate (MSU) crystal deposition, which activates innate and adaptive immune responses. Key mechanisms involve NLRP3 inflammasome activation, cytokine release (IL-1β, TNF-α, IL-6), and dysregulated autophagy, positioning GA at the intersection of metabolic and autoimmune disorders. While conventional therapies (colchicine, NSAIDs) remain first-line, their limitations in refractory cases have spurred the development of biologic agents targeting pro-inflammatory pathways. Clinical studies demonstrate that TNF-α inhibitors (etanercept, infliximab), IL-6 blockade (tocilizumab), and autophagy modulators effectively reduce flares and inflammation in treatment-resistant GA. Emerging strategies, including combination therapies and biomarker-guided approaches, highlight the shift toward precision medicine in GA management. This review summarizes current insights into GA’s immunopathogenesis and evaluates the therapeutic potential of immunomodulatory biologics.